Two new species of trichodinid ciliates (Ciliophora: Trichodinidae) from Indian fishes (University Journal of Zoology, Rajshahi University, 2007)
Key words: Trichodina chandae; Trichodina notopterusi; Ciliophora; Trichodinidae; India Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 31-34